Two rare species of Danielsseniinae (Copepoda: Harpacticoida: Pseudotachidiidae) from the Kara and East Siberian Seas, with description of their previously unknown sexes - Garlitska, Lesya; Chertoprud, Elena S. (Zootaxa, 2021)
The previously unknown females of Danielssenia spitsbergensis Gee & Huys, 1994 and males of Mucrosenia kendalli Gee & Huys, 1994 (Pseudotachidiidae, Danielsseniinae) are described based on specimens collected in the Kara and East Siberian Seas.                Females of D. spitsbergensis exhibit the main diagnostic features of the genus Danielssenia Boeck, 1873 (antennule four-segmented; proximal segment of antennary exopod with one seta; structure of all the mouthparts; absence of an inner seta on exopod-1 of P2–P4; P5 not fused medially and with distinct exopod and baseoendopod, the latter with five setae; genital field with small copulatory pore and short copulatory duct leading to seminal receptacle with paired anterior chambers). At the same time, these specimens also exhibit some distinctive features which are unique for the species but disagree with the generic diagnosis. These peculiarities validate the placing of D. spitsbergensis as species incertae sedis within Danielssenia and point out the necessity of examination of other ‘Danielssenia-like’ forms before the true taxonomic position of this species can be elucidated.                Both males and females of M. kendalli exhibit the autapomorphies of the genus, viz. P2 endopod-2 with a mucroniform process reaching almost to end of endopod-3 (this sexually dimorphic character is more pronounced in the males but also present in females); P2 endopod-2 without inner seta; posterior displacement of caudal ramus seta II; presence of tuft of long setules at inner distal corner of caudal ramus; P2 endopod shorter than exopod; P2–P4 exopod-1 without inner seta. Furthermore, some particular features (anal somite and pseudoperculum morphology; female P1 endopod distinctly longer than exopod; P5 exopod with distinct suture on dorsal surface separating it from the baseoendopod; prominent mucroniform process on P2 endopod-2) of the Kara and East Siberian Sea specimens conform fully with the original description of M. kendalli but apparently differ from M. kliei (Smirnov, 1946), the single female of which was collected from the same region and depth. Therefore, the validity and definite status of the specimen described by Smirnov is still a matter of conjecture pending additional findings and, particularly, the discovery of the male.